LEGAL REGIME OF GUARANTEES AND ITS DERIVATIVES - Problems and proposals de lege ferenda - Pajtić, Bojan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
This article is focused solely on the institute of guarantees as collateral in the civil sense, and not to bail in the criminal proceedings, either on bail in customs procedures. However, in addition to traditional guarantees in the legal transactions and practices, derivates of this institute are increasingly important. With the development of economy and banking operations this institutions have been developed too. Due to its characteristics, this institutions enable a higher level of legal security of creditors and others, and simplify and accelerate the process of securing claims. This article is focused on the most important theoretical and practical problems arising from different doctrinal approaches and vagueness of the law in relation to guarantee and institutes that we can call the derivatives of this legal transaction. Specifically, what legal consequences occur after the contract of guarantee, if the guarantor was mistaken in relation to the debtor, thinking that he was not minor? Is guarantor subrogated in case of fulfillment of obligations of the principal debtor (deprived of legal capacity), according to the guarantor? What is the legal effect if guarantor has guaranteed for natural obligations? I believe that this article will provide answers to some of these questions, about which there is no consensus, both in legal theory and in practice. Keywords: guarantee, securing claims, legal capacity, natural obligations, Law on Obligations